1999
DOI: 10.1073/pnas.96.8.4686
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-induced activation of mitogen-activated protein kinase requires mobilization of intracellular calcium

Abstract: Estrogens and growth factors such as epidermal growth factor (EGF) act as mitogens promoting cellular proliferation in the breast and in the reproductive tract. Although it was considered originally that these agents manifested their mitogenic actions through separate pathways, there is a growing body of evidence suggesting that the EGF and estrogen-mediated signaling pathways are intertwined. Indeed, it has been demonstrated recently that 17␤-estradiol (E2) can induce a rapid activation of mitogenactivated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
197
3
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(215 citation statements)
references
References 52 publications
11
197
3
2
Order By: Relevance
“…These e ects are very rapid (5 and 60 s) compared to the 2 ± 60 min response we have described here for activation of MAP kinase. As estrogen-induced activation of MAP kinase is reported to involve mobilization of intracellular calcium (Improta-Brears et al, 1999), it is likely that these very rapid e ects in intracellular calcium concentrations seen with androgens may preceed the activation of MAP kinase reported here in our work. This idea is being investigated at the moment.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These e ects are very rapid (5 and 60 s) compared to the 2 ± 60 min response we have described here for activation of MAP kinase. As estrogen-induced activation of MAP kinase is reported to involve mobilization of intracellular calcium (Improta-Brears et al, 1999), it is likely that these very rapid e ects in intracellular calcium concentrations seen with androgens may preceed the activation of MAP kinase reported here in our work. This idea is being investigated at the moment.…”
Section: Discussionmentioning
confidence: 65%
“…Other mechanisms have been proposed to explain the ER-mediated activation of MAP kinase. In one report it was shown that it occurs via the release of calcium from intracellular stores (Improta-Brears et al, 1999). Another study on the mechanism of ERmediated activation of MAP kinase showed the involvement of Gaq and Gas proteins (Razandi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…1), including the modulation of intracellular calcium [44,55,122,165,175,209] and protein kinase C (PKC; [266,276]). There is also evidence that membrane effects of estrogens can activate intracellular signaling pathways involving cyclic AMP (cAMP; [103,170,254]), protein kinase A (PKA; [104,141,266]), the "mitogen activated protein kinases" (or MAP kinases; [39,122,153,205,260,269,276]), and the tyrosine kinases [39]. The activation of these intracellular signaling pathways results primarily in phosphorylations/dephosphorylations producing different kinds of physiological responses such as the decoupling of a receptor from its effector system [141,[171][172][173] or the modulation of the catalytic activity of an enzyme [191].…”
Section: Non-genomic Effects On Cell Functionmentioning
confidence: 99%
“…The fastest of these effects appear to be associated with the allosteric modulations of ionotropic receptors [190,277,278], but most effects on electrical activity result from a modulation of ion channel activity through G protein linkage (for review see [132,176]). Estrogen-induced changes in intracellular calcium concentrations have also been identified with latencies of a few seconds [44,54,175,209] to several minutes [55,122]. Finally, the time-course of protein phosphorylations and of changes in kinase activity following estradiol treatment ranges between 5 and 30 min [39,122,153,168,260,269,276].…”
Section: Non-genomic Effects On Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation